The Role of Character Education in Public Elementary Schools - Enny Rahayu; Melyani Sari Sitepu; Muti Indah Sari (Indonesian Journal of Education and Mathematical Science, 2023)
Character education is a human activity in which there is an educational action effort whose purpose is for the next generation of the nation.  At the age of elementary school children's growth and development becomes the most important part of their life.  Because a child at that age is likened to a white sheet of paper, the child will accommodate the various information he gets and then will save all the strokes that are written in his memory according to what he gets.  This research article aims to get an overview of how teacher behavior and character education can improve the quality of education in Indonesia, especially at SDN 105416 Sei Rejo.  The method used is a qualitative method and the technique used is a type of literature review research.  The subjects in this study were teachers and students, the objects in this study were character education in elementary schools.  Character education aims to improve the quality of implementation and results of education in schools that lead to the achievement of the formation of character and noble character of students as a whole.